2016
DOI: 10.1590/s1983-41952016000100006
|View full text |Cite
|
Sign up to set email alerts
|

The influence of recycled concrete aggregates in pervious concrete

Abstract: ResumoThe expansion of urban areas under constant changes in the hydrological cycle directly affects the drainage of rainwater. The problems of urban drainage become major engineering problems to be solved in order to avoid negative consequences for local populations. Another urban problem is the excessive production of construction and demolition waste (CDW), in which , even with a increasingly policy of waste management , have been an end up being thrown in inappropriate disposal sites. Alternatively aiming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…A possible justification for the inferior results would be the nature and characteristic of the recycled coarse aggregate, they are heterogeneous materials, that is, of an uneven nature and composed of different elements, they also have a higher porosity compared to natural waste, resulting in greater porosity in concrete and as a consequence, a lower capacity with reduced compressive strength. This material becomes harmful to structural elements, which due to its pores, reduces the ability to prevent corrosion in the armatures (TAVARES;KAZMIERCZAK, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…A possible justification for the inferior results would be the nature and characteristic of the recycled coarse aggregate, they are heterogeneous materials, that is, of an uneven nature and composed of different elements, they also have a higher porosity compared to natural waste, resulting in greater porosity in concrete and as a consequence, a lower capacity with reduced compressive strength. This material becomes harmful to structural elements, which due to its pores, reduces the ability to prevent corrosion in the armatures (TAVARES;KAZMIERCZAK, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Çetin (2015) incorporated recycled household plastics (low density polyethylene [LDPE]) as a supplemental aggregate (1, 3, and 6%) in porous asphalt to produce a permeable plastic pavement. Tavares and Kazmierczak (2016) used RCA from construction and demolition waste in pervious concrete and found that mean 28-day compressive strengths were within the expected range (2.8 -28 MPa or 400 -4000 PSI) for pervious concrete. David et al (2018) found similar performance characteristics when comparisons of compressive strength, density and surface infiltration rate of pervious concrete containing RAP and waste tire rubber were made with pervious concrete that was made up of natural aggregate without additions.…”
mentioning
confidence: 94%
“…Numerous researchers (Nishigaki 2000, Rizvi et al 2010, Bhutta et al 2013, Çetin 2015, Jang et al 2015, Khankhaje et al 2017, Monrose et al 2019, Yao et al 2019, Tavares and Kazmierczak 2016, David et al 2018 have reported on the incorporation of recycled waste materials or recycled industrial by-products in permeable pavement surfaces, porous concrete in particular. Nishigaki (2000) used blast furnace slag in permeable paving blocks.…”
mentioning
confidence: 99%
“…En este orden de ideas, el reemplazo de AR a la mezcla que sustituye al agregado grueso genera una mezcla con mayor porosidad obteniendo grandes ventajas para el drenaje de aliviaderos, pero también con deficiencias que afectan la resistencia mecánica, originando algunos riesgos en la estructura [29]. En efecto, la relación agua-cemento (A/C), reposición parcial de agregado grueso por agregado reciclado, intervienen en las propiedades, tanto físicas, como mecánicas, para generar el concreto permeable [30].…”
Section: Introductionunclassified